ASEAN Digital Masterplan: Responding Cyber Security Dilemma in The Post-Covid Era (Global Focus, 2022)
The COVID-19 pandemic has brought people to stay longer to disconnected from the face-to-face world than before and rely on the cyber domain daily. Because of the pandemic, Southeast Asia countries added a new 40 million internet users and in total 400 million internet users in the region. The new environment of interaction in the virtual domain generates the bipolarity of dominant power between the U.S and China to establish how cyberspace needs to regulate. The increasing penetration of internet users in the region creates an opportunity for ASEAN to establish ASEAN digital master plan that aims to accelerate region recovery from the pandemic through cyber cooperation. Despite ASEAN as a regional institution promote openness and freedom of cyber domain among its members, ASEAN member states taking contradiction policy to its regional institution. This research tries to answer why ASEAN member states take contradiction policy to their regional institution. Utilizing government politic model theory and insecurity dilemma concept, the author argues that insecurity dilemma that faced by ASEAN member states shaping its member states taking an opposite policy of connectivity on cyberspace that regional institution digital masterplan aim for.